KEPEMIMPINAN INOVATIF DALAM IMPLEMENTASI PELAYANAN PUBLIK (Studi Kasus di Kantor Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Kerinci): PEBI JULIANTO - JULIANTO, S.Sos., MM., CHt, PEBI (LPPM STIA Nusantara Sakti, 2023)
Innovative leadership style in the implementation of public services (a case study in the Kerinci district population and civil registration service) The formulation of the problem in this study is, how does the innovative leadership style in the Kerinci district population and civil registration service cope with the soaring people who need services with innovations owned by the relevant department. This study uses a qualitative approach where the data obtained through field interviews with 6 informants refers to 4 research indicators namely, 1. Findings or ideas 2. Selection of ideas 3. Implementation of ideas 4. Dissemination of ideas. The data obtained in the field were analyzed based on the classification of the informants' answers which were described in the results and discussion of the research which were then carried out by interpretive researchers. It is known that the innovative leadership style in the implementation of public services at the Kerinci district population and civil registration office, from four indicators has been well implemented, but the authors suggest that the apparatus can continue to strive to create the latest innovations to make it easier for people who receive services.